Hubungan Strategi Promosi Kesehatan Dengan Angka Kejadian Stunting Pada Balita Di Pidie Jaya Provinsi Aceh - R, Ramadhaniah; Walidin, Bahrol (Politeknik Negeri Jember, 2025)
The Trienggadeng health center report has toddlers who are stunted at 25.7%, due to the fact that the health center does not carry out an optimal health promotion strategy through atmosphere building and empowering village cadres in providing information to the community about stunting prevention, but advocacy has been carried out with the existence of a stunting prevention policy by the health center, namely providing additional food for toddlers, and health counseling at Posyandu. This study aims to determine the health promotion strategy to reduce stunting rates in children under five in the Trienggadeng Health Center Working Area, Pidie Jaya Regency in 2021. This research is descriptive analytic with a cross sectional design. Data collection was carried out by interview using a questionnaire. The study's population comprises all mothers with toddlers, totaling 1,491, and the sample size was determined using a proportional sampling technique, resulting in 94 toddlers. This research was conducted on April 07-29, 2021 in 27 villages. The statistical test used is the Chi Square Test (α = 95%).The results of univariate research show that toddlers who are stunted (67%), there is no advocacy (64.9%), no atmosphere building (62.8%), and no community empowerment (63.8%). The results of the bivariate statistical test obtained there is a relationship between advocacy (p value = 0.001), atmosphere building (p value = 0.001), community empowerment (p value = 0.002), with health promotion strategies in reducing stunting in toddlers in the Trienggadeng Health Center working area, Pidie Jaya Regency in 2021. The conclusion of this study is that advocacy, atmosphere building and community empowerment are factors that influence health promotion strategies in reducing stunting in toddlers in the Trienggadeng Health Center working area. It is recommended that health center officers focus on health promotion by implementing strategies through community empowerment with an individualized approach at Posyandu